Domestic abuse: an exploration of socio-cognitive factors - Mann, Sophie (2024)
Background: Domestic abuse is a prevalent and persistent problem affecting over two million people a year in the UK, despite decades of research, new government legislation and intervention programmes. Aims: This thesis aims to gain further understanding about domestic abuse perpetration in the community and the relationship between socio-cognitive factors and domestic abuse. Methods: Four studies were completed, using a variety of methods: firstly, the properties and effectiveness of a police risk assessment tool for domestic abuse were evaluated. Secondly, a systematic review explored cognitive factors in domestic abuse perpetrators, which were then further explored in a research study which utilised three measures to assess theory of mind abilities, adverse childhood experiences and domestic abuse perpetration. Finally, a case study considered how adapting an intervention with awareness of socio-cognitive difficulties and specifically targeting these may support someone with domestic abuse and violence history. Results: The police risk assessment tool was not fit for purpose, with a new tool now utilised by police. Domestic abuse perpetrators were found to have cognitive and socio-cognitive difficulties in the review, also associated with adverse childhood experiences. This was supported by results from the research study, specifically exploring theory of mind. Finally, the case study demonstrated a reduction in aggression over a 6-month intervention, targeting emotion regulation and socio-cognitive skills. Discussion: Socio-cognitive abilities appear important to consider in relation to domestic abuse development and perpetration, which are not currently included in assessment or interventions. Understanding more about how these abilities may affect other known trajectories and risk factors may increase our ability to prevent, reduce and manage domestic abuse perpetrators and support victims.